ICARE-Based Animated Video Learning Media on Data Presentation in Mathematics for Fourth Grade Elementary School Students - Darmayanti, Ni Nyoman Yunita; Agustika, Gusti Ngurah Sastra; Chindytia (International Journal of Natural Science and Engineering, 2025)
Student learning outcomes in mathematics, particularly in data presentation, are still relatively low. This is due to the use of conventional teaching methods that are uninteresting and unsuited to students' learning styles, resulting in poor conceptual understanding and low motivation to learn. This study aims to create an ICARE-based animated video medium. This is a research and development (R&D) study using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The research subjects include subject matter experts, instructional designers, learning media specialists, and 32 fourth-grade students. Data were collected using Likert scale questionnaires and multiple-choice tests, while the instruments used were questionnaire sheets and test sheets. Data were analyzed using quantitative descriptive statistics and a one-sample t-test. The results of the study indicate that the developed animated video media have excellent quality based on expert evaluations and student trials. In conclusion, the use of animated video media based on the ICARE model in data presentation materials can enhance students' conceptual understanding and learning motivation in fourth-grade elementary school. Implications suggest that the application of this media can serve as an innovative alternative to improve the quality of mathematics education and support more interactive and engaging learning methods for students.